Regulation of somatostatin secretion from pancreatic δ-cells - Vergari, E (2016)
The somatostatin-secreting δ-cell is the least abundant cell type in the pancreatic islet and this may explain why very little is known about its role and function. In this thesis, I have characterized the SST-Cre-GCaMP3 mouse model in which the genetically encoded Ca2+ sensor GCaMP3 is expressed in somatostatin-expressing cells. Using these mice, glucose-induced somatostatin secretion was found to be inhibited by a KATP channel-dependent membrane depolarization and amplified by Ca2+ -induced Ca2+ release (CICR) mediated by activation of ryanodine receptor Ca2+ release channels. Interestingly, glucose-induced [Ca2+ ]i oscillations in δ-cells did not correlate with electrical activity and persisted also when the cells were clamped at -70 mV, consistent with an important role of CICR. In addition, this study led to the finding that [Ca2+ ]i oscillations in different δ-cells display a synchronous behaviour upon glucose stimulation. The role of somatostatin in the paracrine regulation of glucagon secretion was also addressed. Application of insulin inhibited glucagon secretion and stimulated somatostatin release. Using the SST-GCaMP3 mice, it was demonstrated that insulin exerts a direct stimulatory effect on δ-cells [Ca2+ ]i oscillations. After δ cell-specific ablation of insulin receptor, insulin had no inhibitory effect on glucagon secretion. This was paralleled by the loss of insulin-induced stimulation of somatostatin secretion. Collectively, these data suggest that insulin stimulates somatostatin release, which in turn inhibits glucagon secretion. This finding highlights the pivotal role of somatostatin in the regulation of glucagon secretion. It also raises the interesting possibility of using a somatostatin receptor antagonist as an adjunct to insulin therapy to minimize the risk of hypoglycaemia.